Dual tumor- and subcellular-targeted photodynamic therapy using glucose-functionalized MoS2 nanoflakes for multidrug-resistant tumor ablation - Sumati Bhatia (Biomaterials, 2022)
Photodynamic therapy (PDT) is emerging as an efficient strategy to combat multidrug-resistant (MDR) cancer. However, the short half-life and limited diffusion of reactive oxygen species (ROS) undermine the therapeutic outcomes of this therapy. To address this issue, a tumor-targeting nanoplatform was developed to precisely deliver mitochondria- and endoplasmic reticulum (ER)-targeting PDT agents to desired sites for dual organelle-targeted PDT. The nanoplatform is constructed by functionalizing molybdenum disulfide (MoS2) nanoflakes with glucose-modified hyperbranched polyglycerol (hPG), and then loading the organelle-targeting PDT agents. The resultant nanoplatform Cy7.5-TG@GPM is demonstrated to mediate both greatly enhanced internalization within MDR cells and precise subcellular localization of PDT agents, facilitating in situ near-infrared (NIR)-triggered ROS generation for augmented PDT and reversal of MDR, causing impressive tumor shrinkage in a HeLa multidrug-resistant tumor mouse model. As revealed by mechanistic studies of the synergistic mitochondria- and ER-targeted PDT, ROS-induced ER stress not only activates the cytosine-cytosine-adenosine-adenosine thymidine/enhancer-binding protein homologous protein (CHOP) pro-apoptotic signaling pathway, but also cooperates with ROS-induced mitochondrial dysfunction to trigger cytochrome C release from the mitochondria and induce subsequent cell death. Furthermore, the mitochondrial dysfunction reduces ATP production and thereby contributes to the reversal of MDR. This nanoplatform, with its NIR-responsive properties and ability to target tumors and subcellular organelles, offers a promising strategy for effective MDR cancer therapy.